CREATING A DICTIONARY OF CHEMISTRY AND BIOLOGY TERMS IN ENGLISH AND UZBEK LANGUAGES - Nabijonova , Nilufar Mirmuxsin qizi; Uzaqova , Ma’muraxon Matkarimovna (Innovative Development in Educational Activities, 2023)
The creation of a comprehensive dictionary of scientific terminology is essential for effective communication and knowledge dissemination in the fields of chemistry and biology. This article outlines the fundamental principles involved in creating a dictionary of chemistry and biology terms in English and Uzbek languages, to provide a systematic approach to the creation and organization of the dictionary. The dictionary will serve as a valuable resource for students, researchers, and professionals in the field of chemistry and biology